Achieving Ultralow, Zero, and Inverted Tunneling Attenuation Coefficients in Molecular Wires with Extended Conjugation. Issue 12 (4th February 2021) - Lee, Hyun Ju; Cho, Soo Jin; Kang, Hungu; He, Xin; Yoon, Hyo Jae
Abstract: Molecular tunnel junctions are organic devices miniaturized to the molecular scale. They serve as a versatile toolbox that can systematically examine charge transport behaviors at the atomic level. The electrical conductance of the molecular wire that bridges the two electrodes in a junction is significantly influenced by its chemical structure, and an intrinsically poor conductance is a major barrier for practical applications toward integrating individual molecules into electronic circuitry. Therefore, highly conjugated molecular wires are attractive as active components for the next‐generation electronic devices, owing to the narrow highest occupied molecular orbital–lowest occupied molecular orbital gaps provided by their extended π‐building blocks. This article aims to highlight the significance of highly conductive molecular wires in molecular electronics, the structures of which are inspired from conductive organic polymers, and presents a body of discussion on molecular wires exhibiting ultralow, zero, or inverted attenuation of tunneling probability at different lengths, along with future directions. Abstract : In molecular electronics, molecular wires based on extended π‐building blocks can be attractive active components for developing next‐generation electronic devices. This review describes unconventional length‐dependences—ultralow, zero, or inverted attenuation of tunneling probabilities—in molecular tunneling junctions with highly π‐conjugated and conductive molecular wires. The mechanism of such attenuation behaviors and structure–property relationships are discussed.